1980
DOI: 10.1172/jci109718
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine-induced Insulin Resistance in Man

Abstract: A B S T R A C T Endogeniouis release of epiinephlrine alter stress as well as exogenouis epinephrine infusion are known to resuilt in imiipaired glucose tolerance. Previouis stuidies of man and animals have demonoestrated that this effect of epinephrine results fromn inhibitioni of insulin secretion and aiugiimentation of hepatic glucose production. However, the effect of epiniephrine oii tissue sensitivity to insulin, and the relative contribuitions of peripheral vs. hepatic resistanice to imnpairedl insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
254
5
4

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(281 citation statements)
references
References 22 publications
11
254
5
4
Order By: Relevance
“…Blockade of β 2 ‐receptors seems to have a more profound effect than blockade of β 1 ‐receptors 5, 18. In addition, sympathetic activation can decrease the secretion of leptin,17 exacerbate insulin resistance,18 and promote the release of proinflammatory cytokines,19 all of which can lead to wasting of adipose and muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of β 2 ‐receptors seems to have a more profound effect than blockade of β 1 ‐receptors 5, 18. In addition, sympathetic activation can decrease the secretion of leptin,17 exacerbate insulin resistance,18 and promote the release of proinflammatory cytokines,19 all of which can lead to wasting of adipose and muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of insulin resistance is multifactorial and has been related to hormonal and metabolic abnormalities [13,[31][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51]. In contrast with Type 1 diabetes, in chronic renal failure high polypeptide hormone levels, are not necessarily the result of hypersecretion, but can be due to clearance defects.…”
Section: Discussionmentioning
confidence: 99%
“…There is also direct evidence contrary to the hypothesis that blood flow is an independent regulator of insulin-stimulated glucose uptake in humans [17]. In view of the contradictory data, we studied the relation between muscle blood flow and metabolism during b-adrenergic stimulation, which is known to induce insulin resistance as well as peripheral vasodilation [1]. In a recent study on the human leg, the haemodynamic effects exerted by epinephrine were suggested to be an important compensating factor for the altered insulin sensitivity [18].…”
mentioning
confidence: 95%
“…
Epinephrine and b-adrenergic stimulation rapidly inhibit insulin-mediated glucose uptake by induction of insulin resistance mainly in the skeletal muscle [1,2]. The insulin signalling pathway may be altered by b-adrenergic stimulation both by cAMP and cAMP independent mechanisms [3].
…”
mentioning
confidence: 99%